(untitled) (American Innovator: Journal of Emerging Technologies and Research, 2026)
The Oqdaryo Reservoir (40°12′N, 65°48′E; surface area 178 km², capacity 2.1 km³) represents a critical water resource in the arid conditions of Central Asia. Understanding the biodiversity and ecological roles of its primary producers is essential for evidence-based reservoir management and water quality monitoring.